2005
DOI: 10.1002/hrm.20073
|View full text |Cite
|
Sign up to set email alerts
|

Sellers or keepers? Stock retentions in stock option plans

Abstract: This article examines stock-holding behaviors among participants in Save As

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(60 reference statements)
2
10
0
Order By: Relevance
“…The share plan most likely to be captured by the WERS variable is Sharesave (SAYE): a stock options scheme introduced in 1980 that provides a tax advantageous saving plan mechanism for employees to accumulate the money necessary to exercise discounted options in 3, 5, or 7 years’ time. Although it uses an option structure, SAYE is more akin to a share purchase plan, especially as very few participants fail to exercise their option and around 50 percent of employees retain shares for some time after acquisition (see Pendleton 2005). The share ownership plan dummy is created from two questions: one on the presence of a scheme, and the other on the extent of eligibility among the workforce.…”
Section: Methodsmentioning
confidence: 99%
“…The share plan most likely to be captured by the WERS variable is Sharesave (SAYE): a stock options scheme introduced in 1980 that provides a tax advantageous saving plan mechanism for employees to accumulate the money necessary to exercise discounted options in 3, 5, or 7 years’ time. Although it uses an option structure, SAYE is more akin to a share purchase plan, especially as very few participants fail to exercise their option and around 50 percent of employees retain shares for some time after acquisition (see Pendleton 2005). The share ownership plan dummy is created from two questions: one on the presence of a scheme, and the other on the extent of eligibility among the workforce.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to the first area of implication, the company's decision regarding whether or not to offer employee stock purchase plans may be impacted by their knowledge of the workforce and its demographic and other characteristics. Prior research has indicated that age, income, and risk preferences are all associated with participation in stock purchase plans (Pendleton, ). The current study indicates that looking beyond these demographic variables is important because the organization‐based identity demonstrated a stronger relationship with employee participation in these plans than does age and income in this particular sample.…”
Section: Discussionmentioning
confidence: 99%
“…The control variables utilized in the analyses include age, tenure, salary, pay satisfaction, benefit satisfaction, pay transparency, perceptions of company performance, job satisfaction, management information sharing, and risk attitudes. Demographic variables, such as age, tenure, and salary, have been shown to play a role in predicting stock purchase plan participation (Faigen, Mygind, Sigurjonsson, & Arnardottir, ; Pendleton, ). Three of the control variables (pay, benefit satisfaction, and pay transparency) deal directly with one's view of their total compensation and are therefore likely to factor into one's decision to participate in a stock purchase plan (Faigen et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have focused instead on determinants of firms' implementation of such programs (e.g., Babenko et al, 2011;Chaplinsky & Niehaus, 1994). Although some of these studies do consider the influence of the institutional environment (e.g., Poutsma et al, 2003), to the best of our knowledge, no study has investigated only when they can afford it (Pendleton, 2010b), are of an age at which saving and investing becomes relevant (Babenko & Sen, 2014;Pendleton, 2010b) (these reasons also matter for individuals' decision to retain stock [Pendleton, 2005]), and are well informed about the program (Klein et al, 1988). We complement this research by adding the aspect of evaluation and thereby the theoretical perspective of bounded rationality.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the research on determinants of individual ESOP participation has focused on either demand or supply arguments. Previous research has demonstrated that employees invest only when they can afford it (Pendleton, ), are of an age at which saving and investing becomes relevant (Babenko & Sen, ; Pendleton, ) (these reasons also matter for individuals' decision to retain stock [Pendleton, ]), and are well informed about the program (Klein et al, 1988). We complement this research by adding the aspect of evaluation and thereby the theoretical perspective of bounded rationality.…”
Section: Discussionmentioning
confidence: 99%